1971
DOI: 10.1088/0031-9155/16/2/313
|View full text |Cite
|
Sign up to set email alerts
|

Thermoluminescence response of 7LiF to ultra-violet light

Abstract: I t has been shown that re-estimation of radiation dose is possible with 'LiF thermoluminescence dosemeters using ultra-violet light. The thermoluminescenoe response t o U.V. radiation and the optical absorption of 'LiF have been examined and the possibilities of this method of dose re-assessment are indicated. It is suggested that the thermoluminescence response to U.V. light is due to the presence of deep trapping centres which are bleached by suitable optical wavelengths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

1973
1973
1995
1995

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 4 publications
0
6
0
1
Order By: Relevance
“…Horowitz et a1 (1979d) measured the angular distribution of the thermal-neutron radiation field produced by a 11 1 GBq (3Ci) Am-Be source at a point 11 cm from the source in a 1.5 m3 water tank and showed that the 3.5% change in &/q5 due to the anisotropy can result in a 70% error in the gamma dose if the anisotropy is not taken into account. (1980)) as an ionisation density discriminator (Busuoli et a1 1970, Mason 1970, Furuta and Tanaka 1972, Endres and Lucas 1974, Nash and Johnson 1977, Driscoll 1978, Tuyn 1980, Hoffman and Moller 1980, however, the batch dependence of ET=., the composite nature of the high-temperature glow peak component and the difficulty of accurate separation from peak 5 renders this technique of limited reliability. A similar glow peak dependence on ionisation density has been observed for CaF2:Tm (TLD-300, Harshaw) where the high-temperature peak at 250 "C shows a greater sensitivity to fast neutrons that the 150 "C peak (Griffith et a1 1979 and references therein).…”
Section: 41mentioning
confidence: 99%
“…Horowitz et a1 (1979d) measured the angular distribution of the thermal-neutron radiation field produced by a 11 1 GBq (3Ci) Am-Be source at a point 11 cm from the source in a 1.5 m3 water tank and showed that the 3.5% change in &/q5 due to the anisotropy can result in a 70% error in the gamma dose if the anisotropy is not taken into account. (1980)) as an ionisation density discriminator (Busuoli et a1 1970, Mason 1970, Furuta and Tanaka 1972, Endres and Lucas 1974, Nash and Johnson 1977, Driscoll 1978, Tuyn 1980, Hoffman and Moller 1980, however, the batch dependence of ET=., the composite nature of the high-temperature glow peak component and the difficulty of accurate separation from peak 5 renders this technique of limited reliability. A similar glow peak dependence on ionisation density has been observed for CaF2:Tm (TLD-300, Harshaw) where the high-temperature peak at 250 "C shows a greater sensitivity to fast neutrons that the 150 "C peak (Griffith et a1 1979 and references therein).…”
Section: 41mentioning
confidence: 99%
“…It has been shown previously that the intrinsic UV sensitivity of many bulk TL dosimeters 8,9 arises due to phenomena associated with the surface of the phosphors. Lithium fluoride dosimeters 8 were found to have increasing UV sensitivity for smaller grain sizes due to the larger surface area of the smaller grains.…”
Section: Ultraviolet Dosimetry Using Thermoluminescence Of Semiconducmentioning
confidence: 99%
“…In PTTL a TLD is exposed to ionizing radiation and annealed to a temperature high enough to empty the low-temperature traps but keeping intact the hightemperature traps. Then, the TLD is exposed to light, UV being the most efficient, causing charge transfer (Mason 1971, Jain 1984. T h e w exposure re-populates the low-temperature peaks at the expense of the high-temperature peaks which are then seen to be depleted.…”
Section: Esfect Of the Submicrometre Ai Windowmentioning
confidence: 99%